A Reciprocal Linkage between Self-Regulated Learning and Learning Related Emotions: Investigating Relations Differences across Gender and Study Tracks - Jdaitawi, Malek (DIRASAT: EDUCATIONAL SCIENCES, 2016)
The aim of this study is to investigate the relationship between self-regulated and learning related emotions in a university context. In addition, this study looks into the differences in self-regulated levels between the genders. Furthermore, the study also determined the significant relationship between self-regulated and learning emotions based on gender and study tracks variables. The study’s sample comprised 209 university students. 120 students were males and 89 were females. The results revealed that there was a relationship between self-regulated and learning related emotions. According to the findings, the relationship between the study variables does not significantly differ between genders. Furthermore, differences of the relationship between self-regulated and learning related emotions were noted in terms of study tracks. The study explores implications of the significance of self-regulated and students learning emotions in the university environment and makes recommendations in light of these implications.